2007
DOI: 10.1007/s11916-007-0219-z
|View full text |Cite
|
Sign up to set email alerts
|

The role of myofascial trigger points in musculoskeletal pain syndromes of the head and neck

Abstract: Neck and head pain syndromes are common problems seen in clinical practice. Pain features of commonly designated idiopathic neck pain and some primary headaches (ie, tension-type headache or migraine) fit the descriptions of referred pain originating in muscle trigger points (TrPs). This article discusses the scientific evidence supporting the role of muscle TrPs in chronic musculo-skeletal disorders of the neck and head. The relevance of referred pain elicited by muscle TrPs in patients with neck pain has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(65 citation statements)
references
References 76 publications
1
56
0
3
Order By: Relevance
“…Furthermore, pain evoked from an MTrP by noxious electrical stimulation is associated with significantly enhanced activity in brain regions involved in sensorydiscriminative and affective processing compared with controls [29]. Headache pain can be reproduced by local and referred pain from active MTrPs [24], and migraine symptom resolution and PPT increase are achieved following consecutive MTrPs' anesthetic infiltration [30]. Even more, activation of a latent MTrP by sustained mechanical stimulation in the upper arm can decrease PPT in the tibialis anterior muscle in healthy subjects (Xu et al, unpublished data).…”
Section: Active Myofascial Trigger Points Contribute To Central Sensimentioning
confidence: 95%
See 1 more Smart Citation
“…Furthermore, pain evoked from an MTrP by noxious electrical stimulation is associated with significantly enhanced activity in brain regions involved in sensorydiscriminative and affective processing compared with controls [29]. Headache pain can be reproduced by local and referred pain from active MTrPs [24], and migraine symptom resolution and PPT increase are achieved following consecutive MTrPs' anesthetic infiltration [30]. Even more, activation of a latent MTrP by sustained mechanical stimulation in the upper arm can decrease PPT in the tibialis anterior muscle in healthy subjects (Xu et al, unpublished data).…”
Section: Active Myofascial Trigger Points Contribute To Central Sensimentioning
confidence: 95%
“…It is important to note that central sensitization mechanisms are not specific for FM; they also are involved in different regional musculoskeletal pain syndromes due to MTrPs, such as low back pain [22], neck shoulder pain [23], headaches [24], knee pain [25], and pelvic pain [26]. Central sensitization in FM and local pain syndromes may be one of degree and not of qualitative difference.…”
Section: Active Myofascial Trigger Points Contribute To Central Sensimentioning
confidence: 99%
“…[13][14][15] Although many studies [16][17][18][19] reported that patients with neck pain had trigger points in the cervical and shoulder muscles, such as the upper trapezius muscle, few authors have studied trigger points as the main cause of neck pain.…”
Section: ª 2015 By the American Congress Of Rehabilitation Medicinementioning
confidence: 99%
“…Se ha descrito que el DMF proveniente de diferentes músculos craneales y cervicales puede jugar un rol importante en la génesis del dolor en la región craneocervical (9,11) representado a través de diferentes estudios epidemiológicos que lo consideran una importante fuente de dolor musculoesquelético (11). En la región orofacial y cervical, se ha sugerido que el DMF se puede expresar como una cefalea tipo tensional (12) dado que los impulsos nociceptivos periféricos de los músculos actúan como zonas de hiperalgesia primaria conduciendo a una sensibilización central y por consiguiente a una cefalea tipo tensional (13).…”
Section: Generalidades Del Dolor Miofascialunclassified